Integrating Disaster Accounting, Climate Change Disclosure, And Climate Justice: Towards A Unified Framework For Sustainability Reporting - Anthony Oyamendan; Babatunde Afolabi; Egunlusi Femi Bamidele (Universitas Indonesia Membangun, 2025)
Climate change and disasters pose growing challenges for businesses and societies. Accounting plays a key role in capturing these risks and advancing fair and sustainable responses. This study investigates how disaster accounting, climate change disclosure, and climate justice are integrated into global accounting practices. The study draws on secondary data from sustainability reports of multinational corporations and international standards such as the GRI, IFRS, and TCFD. Structured content analysis and descriptive statistics were applied to evaluate disclosure patterns across industries and regions. Findings show that climate change accounting is becoming relatively standardized. In contrast, disaster-related reporting is fragmented, and climate justice is largely absent from disclosures. Significant sectoral and regional differences were observed. Energy and manufacturing firms, and corporations in developed regions, reported at higher levels. Firms in developing economies disclosed selectively or minimally. Correlation and regression analyses confirm that industry type and geographical context strongly influence disclosure depth. The results highlight uneven global progress in embedding sustainability into accounting, with climate justice as the weakest dimension despite its importance for vulnerable communities. Harmonization of standards is urgently required to improve comparability, credibility, and equity in reporting. The study recommends that international standard setters integrate disaster accounting and climate justice into unified frameworks, that developing countries receive capacity-building support, and that governments enforce mandatory sustainability disclosures. By framing disasters and climate change through justice, accounting can help build resilience, strengthen accountability, and support sustainable development worldwide